Review of current evidence in management of oleander poisoning - Vineeth Varghese Thomas; Nalini Newbigging; Jacob Johnson; Murugabharathy Kalimuthu; Karthik Gunasekaran; Ramya Iyadurai (Current Medical Issues, 2022)
India has a high incidence of poisoning, especially in the rural setting with plant-based compounds being used as a common agent. Oleander poisoning is a common shrub seen throughout the tropics including nearly all parts of India. It continues to remain an important cause for both accidental and deliberate self-harm in the community with all parts of the plant containing toxin sufficient to cause poisoning. There is enough evidence to show that oleander poisoning continues as one of the more common plant-based causes for poisoning. This review looks at the common management principles and provides an update on the currently available treatment strategies and evidence for them.